Development of a portable high-Tc spherical neutron polarimetry device at the Oak Ridge National Laboratory - Nicolas Silva; Tianhao Wang; Sichao Fu; Masaaki Matsuda; Barry Winn; Elynn An; James Beare; Lowell Crow; Kiman Park; Chenyang Jiang (Scientific Reports)
Abstract Spherical neutron polarimetry is a powerful polarized neutron scattering technique used to determine complex magnetic structures which are only partly accessible by other methods. This technique measures the full neutron polarization change upon scattering from a sample by fully decoupling the incoming and outgoing neutron polarization with a zero-field chamber placed at the sample position. Recent advancements and testing are presented for a new spherical neutron polarimetry device utilizing high-Tc superconducting YBCO films, PHiTPAD, at the High Flux Isotope Reactor at Oak Ridge National Laboratory. Furthermore, we introduce a conceptual design that utilizes wavelength-independent adiabatic transitions to adapt spherical neutron polarimetry for use with pulsed neutron sources, thereby expanding its potential applications in neutron scattering research.